VARIOUS SCIENTIFIC APPROACHES TO ‘SLANG’ - Dilafruz Madazizova Xabibiloyevna (Journals Park Publishing, 2022)
Slang is generally considered as informal style of speech which is used by groups of people in particular community. It is a part of language that is usually outside of conventional or standard usage and that may consist of both newly coined words and phrases and of new or extended meanings attached to established terms
Keywords: Communication, informal style, a particular community, phenomena, conventional usage, newly coined words.